A label-free immunosensor for the detection of a new lung cancer biomarker, GM2 activator protein, using a phosphomolybdic acid/polyethyleneimine coated gold nanoparticle composite. Issue 7 (17th February 2021) - Kuntamung, Kulrisa; Sangthong, Padchanee; Jakmunee, Jaroon; Ounnunkad, Kontad
Abstract : A novel electrochemical immunosensor for the detection of a new lung cancer biomarker based on a polyoxometalate-adsorbed poly(ethylenimine)-coated gold nanoparticle modified electrode. Abstract : In this work, we report, for the first time, the construction of a label-free electrochemical immunosensor for highly sensitive detection of a new lung cancer biomarker, GM2 activator protein (GM2AP). A polyethyleneimine-coated gold nanoparticle (PEI-AuNP) and phosphomolybdic acid (PMA) modified electrode is developed as a novel redox platform for GM2AP detection. A PEI-AuNP film-modified screen-printed carbon electrode, as a signal amplifier support, was successfully fabricated for the adsorption of PMA redox molecules and is used for signal amplification. Under the optimized conditions, GM2AP detection is based on a decrease in the current response of PMA redox probes proportionally relative to an amount of the immunocomplex. Our sensor exhibits two linear ranges of 0.005–25 and 25–400 ng mL −1 with a limit of detection (LOD) of 0.51 pg mL −1 . The immunosensor is successfully applied for the determination of GM2AP in both human urine and serum samples. The proposed sensor offers the advantages of simple fabrication, low cost, rapid analysis, satisfactory stability, high selectivity and sensitivity, and good reproducibility. The LOD of the biosensor is approximately 2863 and 1804 fold lower than the clinically relevant levels in human urine and serum, respectively. Our strategy can be used as an alternative non-invasive clinical analysis method for lung cancer screening.